Validation of statistic and deterministic asperity contact models using experimental Stribeck data. (January 2022) - Maier, Michael; Pusterhofer, Michael; Summer, Florian; Grün, Florian
Abstract: Contact models are used, among others, to describe the asperity contact in lubricated contacts. In recent decades, a large number of contact models have been developed based on different approaches. In this article a selection of classical statistical contact models are compared with a deterministic FE model. The validation of the different approaches was carried out applying an indirect methodology. By comparing a numerically determined Stribeck curve, on which the characteristics of the contact model has a significant influence, and experimentally determined Stribeck curves, the applicability of the different contact models can be evaluated. The influence of elastic and elastoplastic material behaviour in the deterministic contact model on the asperity contact pressure curves and Stribeck curves, respectively, was examined during the investigations. The results show, that the elastic FEM contact model and the statistical model according to Greenwood and Tripp provide the best agreement with the experimental Stribeck data. This can be attributed to the fact that the roughness peaks are smoothed immediately in the early contact stage and the smoothed surface behaves almost elastically. Highlights: Comparison of classical statistical and deterministic contact models. Finite Element approach to determine the asperity contact pressure for real rough surfaces. Validation of contact models by comparison of experimental and numerical Stribeck curve data. Coupling of micro- and macromodel to consider the influence of different geometry scales on the frictional behavior.